Tindak Tutur Protokol Kesehatan CHSE di Kawasan Pariwisata Kabupaten Badung Bali - Yohanes Kristianto; Made Budiarsa (Badan Pengembangan dan Pembinaan Bahasa, 2022)
Health protocols set by the central and regional governments are closely related to the use of speech acts that state orders, appeals, and prohibitions both in agencies and in public spaces. This study aims to examine the form, function, and meaning of language in its implementation as a communication medium for health protocols campaigned by the government. CHSE includes Cleanliness, Health, Safety, Environment. CHSE is one of the strategies of the Ministry of Tourism and Creative Economy in restoring the tourism sector. The method used in this study is a qualitative descriptive with a natural setting to examine the dynamics of the form, function, and meaning of the health protocol language implemented in the Badung tourism area. The object of this research is illocutionary communicative acts in the language of health protocols. Research data in the form of language forms of health protocols were analyzed using a pragmatic perspective to find out how the context of the situation affects the way of interpreting sentences and utterances related to the language of health protocols by paying attention to certain contexts. Thus, it can be concluded that the CHSE health protocol can simply be referred to as a public service advertisement or commonly referred to as a social campaign using illocutionary communicative speech acts. The implications of this study can be used as a reference in designing a Health protocol language that is more effective and efficient for tourist destinations in Badung Regency, Bali. AbstrakProtokol kesehatan yang ditetapkan oleh pemerintah pusat maupun daerah sangat terkait dengan penggunaan tindak tutur yang menyatakan perintah, himbauan, dan larangan baik di instansi maupun di ruang publik. Penelitian ini bertujuan untuk mengkaji bentuk, fungsi, dan makna bahasa dalam implementasinya sebagai media komunikasi protokol kesehatan yang dikampanyekan oleh pemerintah. CHSE meliputi Cleanliness (kebersihan), Health (kesehatan), Safety (keamanan), Environment (ramah lingkungan). CHSE merupakan salah satu strategi Kementerian Pariwisata dan Ekonomi Kreatif dalam memulihkan sektor kepariwisataan. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif dengan setting alamiah untuk mengkaji dinamika bentuk, fungsi, dan makna bahasa protokol kesehatan yang diiplementasikan di kawasan pariwisata Badung. Objek dalam penelitian ini adalah tindak komunikatif ilokusi pada bahasa protokol kesehatan. Data penelitian yang berupa bentuk-bentuk bahasa protokol kesehatan dianalisis menggunakan perspektif Linguistik Pragmatik untuk mengetahui bagaimana konteks situasi mempengaruhi cara menafsirkan kalimat dan ujaran-ujaran berkaitan dengan bahasa protokol kesehatan dengan memperhatikan konteks tertentu. Hasil kajian dapat disimpulkan bahwa protokol kesehatan CHSE merupakan iklan layanan masyarakat dalam bentuk tindak tutur komunikatif ilokusi. Implikasi kajian ini dapat digunakan sebagai acuan dalam merancang Bahasa protocol Kesehatan yang lebih efektif dan efisien bagi para pengelola destinasi wisata di Kabupaten Badung, Bali.